THE EFFECT OF OUTPATIENT SERVICE QUALITY ON BPJS HEALTH PARTICIPANTS' SATISFACTION AT BALIMBINGAN HOSPITAL, SIMALUNGUN REGENCY, INDONESIA - Dony Hermanto Saragih; Ermi Girsang; Sri Lestari Ramadhani Nasution (Journal of Gender and Social Inclusion in Muslim Societies, 2026)
Evaluating the quality of healthcare services is crucial for improving patient satisfaction and building long-term trust in institutions within the BPJS Kesehatan ecosystem, particularly in regional healthcare facilities. This study aims to empirically analyze the simultaneous and partial effects of service quality dimensions based on the modified SERVQUAL framework (tangibles, reliability, responsiveness, assurance, and commitment) on the satisfaction of BPJS Kesehatan outpatient participants at Balimbingan Hospital, Simalungun Regency. A quantitative observational study with a cross-sectional design was conducted in March 2026. A total of 208 outpatient respondents were recruited via convenience sampling. Data were collected using a modified structured questionnaire with 25 items that had been validated and tested for reliability. Statistical analyses included univariate analysis, chi-square tests for bivariate analysis, and multiple logistic regression with the backward-elimination method for multivariate modeling (α = 0.05). Bivariate analysis showed that responsiveness (p = 0.001), reliability (p = 0.000), assurance (p = 0.002), and commitment (p = 0.000) were significantly correlated with patient satisfaction, whereas the physical aspect did not show statistical significance (p = 0.060). The final-stage multiple logistic regression model identified responsiveness and commitment as the only remaining significant predictors. Commitment emerged as the dominant determinant most influential on patient satisfaction (p = 0.003; OR = 4.781; 95% CI = 1.721 to 13.283), followed by responsiveness (p = 0.013; OR = 3.714; 95% CI = 1.322 to 10.428). Staff commitment (affective dedication) and operational responsiveness (prompt care) are critical catalysts in enhancing outpatient satisfaction at Balimbingan Hospital. Hospital management should redirect resource allocation toward professional soft skills development, empathy training, and triage optimization to maintain patient loyalty and competitive advantage.